Determining the depth of meditation through frontal alpha asymmetry - Krishna, Dwivedi; Singh, Deepeshwar; Manjunath, N. K. (Frontiers in Human Neuroscience, 2025)
BackgroundElectroencephalogram (EEG) alpha asymmetry has become a pivotal area of research for understanding functional hemispheric differences in neuroscience. To the best of our knowledge, the relationship between frontal alpha asymmetry (FAA) and the depth of meditation has yet to be thoroughly examined. To address this gap, the present cross-sectional study was conducted to explore the meditative states of long-term meditators and non-meditators.MethodsThis study examined 26 long-term heartfulness meditation practitioners (LTM) and 33 non-meditators (NM), aged 30 to 45 years. Frontal EEG activity was employed to assess frontal alpha asymmetry (FAA), while self-reported measures, including the Meditation Depth Questionnaire (MEDEQ) and the Visual Analogue Scale (VAS), were used to evaluate the depth of meditation.ResultsThe results demonstrated significant differences in self-reported meditation depth between the long-term meditators and non-meditators, as shown through MEDEQ and VAS assessments. Notably, the FAA findings exhibited distinct interaction effects that highlight variations between the two groups. Furthermore, a positive correlation was established between FAA and the depth of meditation, supporting the notion that EEG patterns are reflective of self-reported meditative experiences.ConclusionThe findings suggest that heartfulness meditation may modulate FAA patterns in practitioners, which could be linked to enhanced emotional balance.